PERAN PERPUSTAKAAN DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MADRASAH TSANAWIYAH NEGERI SEKAYU - Trisna Puspita Ningrum (Conciencia, 2017)
This study is entitled "The Role of Libraries in Learning Islamic Education in the State of Sekayu MTs". This study wanted to find out how the library manager at MTs Negeri Sekayu and how big the role of the library was in facilitating student learning at Sekayu State MTs. Organizing a school library must be able to realize and participate in realizing the objectives of primary school administration through the provision and utilization of library materials that have been provided in detail. Because the purpose of the school library is to provide a means for learning, and to help students get the library materials needed both to support learning activities and for reading material. By helping students in learning, the library plays a role in learning. This study uses a qualitative approach, namely focusing attention on efforts to understand the behavior, perceptions and attitudes of the research objectives, as well as its relevance to the formulation of the problem and all the research methods of data collection using observation, interview, documentation, and questionnaire techniques (questionnaire ) Based on these findings it can be concluded that, the manager has given a role as a provider of learning facilities for students by providing complete facilities and infrastructure and providing students with comfort facilities while in the library.